Photoinduced Diffusion Through Polymer Networks. (25th August 2014) - Meng, Yuan; Fenoli, Christopher R.; Aguirre‐Soto, Alan; Bowman, Christopher N.; Anthamatten, Mitchell
<x xml:space="preserve">Abstract</x> Photomediated addition‐fragmentation chemistry is applied to demonstrate the precisely controlled diffusion of chemical species through polymer networks. Fluorescent groups connected to polymer networks by allyl sulfide moieties become mobile upon irradiation with UV light due to radical‐mediated addition‐fragmentation bond exchange. Photoinduced transport through the bulk, into solution, and across film interfaces is demonstrated. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>